Inactivation of Phage MS2 by Iron-Aided Titanium Dioxide Photocatalysis - Sjogren, Jon C. (1994)
Near-UV photocatalytic disinfection was accomplished in aqueous titanium dioxide suspensions. A level of inactivation of phage MS2 of 90% increased to 99.9% after 2 μM ferrous sulfate was added. Hydroxyl radical oxidation, with Fenton reaction enhancement, is suspected to be primarily responsible for the viral degradation observed.